Catalytic Silylations of Alcohols: Turning Simple Protecting-Group Strategies into Powerful Enantioselective Synthetic Methods - Xu, Li-Wen; Chen, Yun; Lu, Yixin (Angewandte Chemie International Edition, 2015)
In recent years, remarkable progress has been made in the enantioselective silylation of alcohols. Owing to the successful site‐ and stereoselective functionalization of hydroxy groups, silyl ether formations have evolved from being a simple reaction for functional‐group protection into a powerful enantioselective process. In this Minireview, we highlight important recent findings in this emerging field. Silicon talks: Owing to the development of methods for the site‐ and stereoselective functionalization of hydroxy groups, silyl ether formation has evolved from being a simple reaction for functional‐group protection into a powerful enantioselective process. This Minireview highlights recent findings in the emerging field of enantioselective alcohol silylation.